The effectiveness of Learning English for economics as perceived by graduate students at felte, ULIS, VNU = Nghiên cứu về sự hiệu quả của việc học môn tiếng anh kinh tế với sinh viên đã tốt nghiệp Khoa Sư Phạm Tiếng Anh, Đại học Ngoại Ngữ, Đại học Quốc gia Hà Nội - Nguyễn, Thị Ngọc Tú (2021)
In this fast-paced life, all over the world people have become highly economic minded. It is believed that the study of economics can provide a solution to many economic and social problems. In any capacity all inhabitants are playing a role as economic agents such as a consumer, an investor or a merchant. It is undeniable that regardless what jobs people do, the Economic knowledge is never futile. The purpose of this study is to identify the effectiveness of English for Economics to FELTE graduates and solutions for its betterment. Quantitative and qualitative methods as survey questionnaires and face-to-face interviews are used to inspect the graduates‟ attitudes towards the effectiveness of English for Economics. These include three major findings. Firstly, although FELTE graduates work in a wide range of jobs, their jobs demand some certain Economics knowledge. Secondly, the purposes of learning English for Economics diversify among FELTE graduates; however; the importance of this subject in practice is undeniable. Last but not least, an appropriate combination of student‟s presentations, material provision and exercise rectifying may be suggested as a new method meeting all the learners‟ demands. A theoretical analysis, backed by analysis of data collection, indicates that English for Economics plays an important role in equipping students at FELTE, ULIS, VNU with necessary Economic background knowledge in their job performance. Some suggestions given to have good results in EC course are: working hard work, being willing to widen knowledge and in-depth understanding about all the lessons. Based on the findings from the research, further studies and future implications may be conducted in a larger population and field to study other relating matters.